THE INFLUENCE OF THE E-TRAINING INFORMATION SYSTEM ON TEACHER PERFORMANCE (Cuea Journal of Business and Economics, 2025)
This study examined the influence of the E-Training Information System (ETIS) on teacher performance in Catholic secondary schools within the Onitsha Archdiocese of Nigeria. A descriptive quantitative design was employed, and stratified random sampling was used to select respondents from 36 schools. Data were gathered via structured questionnaires, and validity was ensured through a pilot test involving 11 participants. The Unified Theory of Acceptance and Use of Technology (UTAUT) guided the study. Correlation analysis revealed a positive and significant relationship between ETIS and teacher performance (r = .403, p < 0.05). Regression analysis showed that ETIS had a statistically significant effect on teacher performance (β = 0.242, p = 0.000), indicating that a one-unit increase in ETIS use corresponds with a 0.242-unit increase in performance. The model explained 49.4% of the variation in teacher performance (R² = 0.494), and the regression was statistically significant (F = 48.370, p = 0.000 < 0.05). ETIS’s user-friendly design, relevant content, accessible resources, mobile compatibility, interactive forums, and efficient assessment tools contributed to its effectiveness. Hypothesis testing confirmed a statistically significant positive relationship between ETIS and teacher performance (p = 0.000, β = 0.242), leading to the rejection of the null hypothesis. The study concludes that implementing interactive, mobile-friendly e-training systems significantly enhances teacher performance. It recommends that Catholic secondary schools adopt robust, user-oriented e-learning platforms to foster continuous professional development.